Strain rate dependence of mode II delamination resistance in through thickness reinforced laminated composites - Yasaee, M; Mohamed, G; Pellegrino, A; Petrinic, N; Hallett, SR (Elsevier, 2017)
A thorough experimental procedure is presented in which the mode II delamination resistance of a laminated fibre reinforced plastic (FRP) composite with and without Z-pins is characterised when subjected to increasing strain rates. Standard three-point End Notched Flexure (3ENF) specimens were subjected to increasing displacement loading rates from quasi-static (∼0 m/s) to high velocity impact (5 m/s) using a range of test equipment including drop weight impact tower and a Modified Hopkinson Bar apparatus for dynamic three-point bending tests. The procedure outlined uses compliance based approach to calculate the fracture toughness which was shown to produce acceptable values of GIIC for all loading rates. Using detailed high resolution imaging relationships between delamination velocities, apparent fracture toughness, longitudinal and shear strain rates were measured and compared. Confirming behaviours observed in literature, the thermosetting brittle epoxy composite showed minor increase in GIIC with increase in strain rate. However, the Z-pinned specimens showed a significant increase in the apparent GIIC with loading rate. This highlights the need to consider the strain rate dependency of the Z-pinned laminates when designing Z-pinned structures undergoing impact.